Effect of Hydrocolloid on Rheology and Microstructure of High-Protein Soy Desserts - Arancibia-Aguilar, C (Springer India, 2015)
Due to the rheological and structural basis of texture perceived in semisolid foods, the aim of this work was to study the effects of two thickening agents, on rheology and microstructure of soy protein desserts. As rheological parameter values may not be enough to explain the possible perceived texture differences, the effect of composition on two instrumental indexes of oral consistency (apparent viscosity at 50 s−1 and complex dynamic viscosity at 8 Hz) was also studied. Samples were prepared at two soy protein isolate (SPI) concentrations (6 and 8 % w/w), each with four modified starch concentrations (2, 2.5, 3 and 3.5 % w/w) or four Carboxymethyl cellulose (CMC) concentrations (0.3, 0.5, 0.7 and 0.9 % w/w). Two more samples without added thickener were prepared as control samples. The flow curves of all systems showed a typical shear-thinning behaviour and observable hysteresis loops. Control sample flow fitted well with the Ostwald-de Waele model and the flow of samples with thickener to the Herschel-Bulkley model. Viscoelastic properties of samples ranged from fluid-like to weak gel, depending on thickener and SPI concentrations. Starch-based samples exhibited a globular structure with SPI aggregates distributed among starch granules. In CMC-based samples, a coarse stranded structure with SPI aggregates partially embedded was observed. Variation of the two thickness index values with composition showed a similar trend with good correlation between them (R2 = 0.92). Soy desserts with different composition but with similar rheological behaviour or instrumental thickness index values can be obtained. © 2015, Association of Food Scientists & Technologists (India).